Pengaruh Lingkungan Kerja Fisik Dan Budaya Kerja Terhadap Produktivitas Kerja Karyawan Divisi Solution Delivery Assurance PT Telkom Kebon Sirih Jakarta Pusat - Afra Fadhilah Putri; Dodi Prasada (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Abstract - This study aims to determine the effect of Physical Work Environment on Employee Productivity, the effect of Work Culture on Employee Productivity, and the simultaneous effect of Physical Work Environment and Work Culture on Employee Productivity at the Solution Delivery Assurance Division of PT Telkom, Kebon Sirih, Central Jakarta. The research method used is quantitative. The sample in this study consisted of 75 respondents, determined through the Slovin formula, with the sampling technique using random sampling. Data analysis methods include simple linear regression, multiple linear regression, coefficient of determination, partial test (t-test), and simultaneous test (F-test). The results of the study show that: (1) Physical Work Environment has a positive and significant effect on Employee Productivity, indicated by a t-value of 2.992 > 1.992 and a significance value of 0.004 < 0.05. (2) Work Culture has a positive and significant effect on Employee Productivity, indicated by a t-value of 6.216 > 1.992 and a significance value of 0.001 < 0.05. (3) Physical Work Environment and Work Culture simultaneously have a positive and significant effect on Employee Productivity, indicated by an F-value of 83.951 > 3.12 and a significance value of 0.001 < 0.05.